(untitled) (International Journal of Environmental Sciences, 2025)
Background: Neck pain is a common musculoskeletal disorder, impacting a significant percentage of the worldwide population. Chronic mechanical neck pain is commonly associated with impaired neuromuscular control and proprioceptive deficits, leading to reduced functional performance and quality of life. Targeted exercise interventions, such as neuromuscular control exercises and proprioceptive training, have been proposed to address these dysfunctions and improve clinical outcomes Purpose: The objective of this study was to compare between the impacts of neuromuscular control exercises and proprioceptive training on neck pain (change in Pain pressure threshold “PPT” and Neck disability index “NDI”) after interventions in adults with chronic mechanical neck pain. Setting: Outpatient Clinic of the Faculty of Physical therapy, Cairo University and Kasr El-Ainy Hospitals, Faculty of Medicine, Cairo University. Methods: A total of sixty patients (both male and female), between the ages of 30 and 45, diagnosed with chronic mechanical neck pain were divided evenly into three groups at random (n = 20 per group). Study Group I were given neuromuscular control exercises (NMCE), which included rolling exercises utilizing upper limb patterns bilaterally, in addition to a standardized physiotherapy program.Study Group II underwent proprioceptive training, consisting of neck position sense exercises and self-stretching routines, alongside the same standardized physiotherapy program.Control Group were given only the standardized physiotherapy program without additional interventions.All participants underwent evaluations both prior to and following the intervention period. Outcome measures included the Neck Disability Index (NDI) for functional assessment of neck pain and an algometer to assess pain pressure threshold (PPT). Results: Both the neuromuscular control exercise (NMCE) group and the proprioceptive training group demonstrated significant improvements in pain and disability outcomes. However, the NMCE group showed a more pronounced reduction in pain intensity and disability. Specifically, there was a statistically significant decrease in Neck Disability Index (NDI) scores and a significant increase in pain pressure threshold (PPT) in the NMCE group compared to both the proprioceptive training group as well as the control group (p < 0.05) following the intervention. Additionally, the proprioceptive training group exhibited a substantial reduction regarding NDI scores as well as a substantial improvement in PPT compared to the control group (p < 0.05) post-treatment. Conclusion: Both neuromuscular control exercises and proprioceptive training were effective in reducing pain and disability in individuals with chronic mechanical neck pain. However, neuromuscular control exercises, when combined with conventional physiotherapy, produced superior outcomes, demonstrating greater improvements in pain pressure threshold along with functional disability compared to proprioceptive training and standard physiotherapy alone.